Effectiveness Of Training On The Neonatal Developmental Care Model In Improving Healthcare Workers’ Knowledge And Attitudes - Syamsu, Andi Fatmawati; Rahim, Rachmawati; Sulisnadewi, Niluh Kompyang; Hadriani; Chen, Hana W.Jun (Jurnal Kesehatan Manarang, 2025)
Premature infants frequently confront developmental obstacles that require close monitoring by medical professionals. The neonatal developmental care model was created to help medical personnel provide interventions that support the healthy development of premature infants in hospitals. The purpose of this study was to evaluate healthcare professionals' attitudes and knowledge regarding the neonatal developmental care model before and after training. This quasi-experimental study with a pre-test and post-test design was conducted from March to October 2024 in the NICU units of RSUD Undata and RSU Anutapura Palu, Indonesia. A total sampling technique was applied to 38 nurses and midwives who met the inclusion criteria. The independent variable was developmental care training, while the dependent variables were the knowledge and attitudes of healthcare workers toward neonatal developmental care. Data were collected using validated questionnaires and analyzed using the Wilcoxon signed-rank test. Following the training, knowledge scores increased by an average (mean rank) of 19.50, and attitude scores increased by an average (mean rank) of 20. The training significantly improved the knowledge and attitudes of healthcare personnel, as indicated by the significance value (p-value) of 0.000 (<0.05) for both variables. The NIDCM training significantly enhanced nurses’ and midwives’ cognitive and attitudinal readiness for developmental care. The integration of structured education and practical learning proved effective in promoting positive behavioral change among healthcare workers. Highlight the importance of institutionalizing developmental care training and strengthening managerial support to ensure sustainable implementation in neonatal settings.